Principles and practice of psychopharmacotherapy - Janicak, Philip G.; Marder, Stephen R., 1945-; Pavuluri, Mani N.; ebrary, Inc. (Philadelphia : Wolters Kluwer Health/Lippincott Williams & Wilkins, 2011)
"Fully updated for its Fifth Edition, Principles and Practice of Psychopharmacotherapy summarizes the latest data on hundreds of drug and device-based therapies and offers practical, evidence-based guidelines and treatment strategies for virtually every psychiatric disorder. Highlights of this edition include expanded coverage of pharmacogenomics, updates on treatments for elderly patients, and discussion of mechanisms of action for drugs used in sleep disorders, especially narcolepsy"--Provided by publisher.
(Publisher-supplied data) General Principles -- Pharmacodynamics and Pharmacokinetics -- Assessment of Drug Efficacy and Relevant Clinical Issues -- Indications for Antipsychotics -- Treatment with Antipsychotics -- Indications for Antidepressants --Treatment with Antidepressants -- Therapeutic Neuromodulation -- Indications for Mood Stabilizers -- Treatment with Mood Stabilizers -- Indications for Antianxiety and Sedative-Hypnotic Agents -- Treatment with Antianxiety and Sedative-Hypnotic Agents -- Assessment and Treatment of Anxiety-Related Disorders -- Psychopharmacotherapy in Early Life -- Psychopharmacotherapy in Later Life -- Psychopharmacotherapy in Special Populations.
Rev. edition of: Principles and practice of psychopharmacotherapy / Philip G. Janicak [and others]. 4th edition c2006.
Includes bibliographical references and index.
Description based on print version record.
Electronic reproduction. Palo Alto, Calif. : ebrary, 2014. Available via World Wide Web. Access may be limited to ebrary affiliated libraries.
Keywords: Mental illness -- Chemotherapy; Psychopharmacology; Electronic books